2018
DOI: 10.3390/biom8040121
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Studies on Compounds Derived from Calceolaria: Phenylethanoid Glycosides as Potential Multitarget Inhibitors for the Development of Pesticides

Abstract: An increasing occurrence of resistance in insect pests and high mammal toxicity exhibited by common pesticides increase the need for new alternative molecules. Among these alternatives, bioinsecticides are considered to be environmentally friendly and safer than synthetic insecticides. Particularly, plant extracts have shown great potential in laboratory conditions. However, the lack of studies that confirm their mechanisms of action diminishes their potential applications on a large scale. Previously, we have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 69 publications
0
30
0
Order By: Relevance
“…For instance, larvicidal inhibitors have the ability to bind to sterol carrier protein-2 [56], juvenile hormone-binding protein [57], D7r4 a salivary biogenic amine-binding protein [58], calcium-dependent protein kinase-1 [59], or purine nucleoside phosphorylase targets [60]. The binding investigation of the dihydroquinazolines against the above-mentioned molecular targets allowed us to identify AChE as the most plausible molecular target which corroborated with the predicted brain cell permeability [51][52][53][54][55][56][57][58][59][60]. No crystal structures of Anopheles arabienesis AChE from mosquito are deposited in the Protein Data Bank (PDB) so far.…”
Section: Molecular Modelingmentioning
confidence: 52%
See 1 more Smart Citation
“…For instance, larvicidal inhibitors have the ability to bind to sterol carrier protein-2 [56], juvenile hormone-binding protein [57], D7r4 a salivary biogenic amine-binding protein [58], calcium-dependent protein kinase-1 [59], or purine nucleoside phosphorylase targets [60]. The binding investigation of the dihydroquinazolines against the above-mentioned molecular targets allowed us to identify AChE as the most plausible molecular target which corroborated with the predicted brain cell permeability [51][52][53][54][55][56][57][58][59][60]. No crystal structures of Anopheles arabienesis AChE from mosquito are deposited in the Protein Data Bank (PDB) so far.…”
Section: Molecular Modelingmentioning
confidence: 52%
“…On the basis of the preliminary structure-activity relationship of the 2,3-dihydroquinazolin-4(1H)-one derivatives, we explored a variety of enzyme molecular targets in an attempt to identify the mode of action via which the compounds exert their larvicidal effect. It is well known that AChE represents the main molecular target of insecticides [51][52][53][54][55] and can be associated with the larvicidal action of our compounds. However, some insecticide enzyme targets other than AChE were reported.…”
Section: Molecular Modelingmentioning
confidence: 99%
“…These compounds possess a particular type of triterpene skeleton, called pachanane, characterized by the presence of five six-membered rings, and the position of the 27α-CH3 attached to C-15 [96,97]. Pachanol A R1 = -, R2 = H, R3 = CH3; △ 12(13), 14 (15) Pachanol B R1 = H, R2 = -, R3 = αCH3; △ 11(12), 13 (18) Pachanol C Pachanol D Although only Mexican columnar cacti were considered to the construction of the present review, a special mention is necessary to describe the triterpene content of Trichocereus pachanoi, a cactus plant from South America, which is an important source of some compounds named pachanols A-D ( Table 7). These compounds possess a particular type of triterpene skeleton, called pachanane, characterized by the presence of five six-membered rings, and the position of the 27α-CH 3 attached to C-15 [96,97].…”
Section: Triterpenes From Mexican Columnar Cactaceaementioning
confidence: 99%
“…These compounds possess a particular type of triterpene skeleton, called pachanane, characterized by the presence of five six-membered rings, and the position of the 27α-CH3 attached to C-15 [96,97]. Pachanol A R1 = -, R2 = H, R3 = CH3; △ 12(13), 14 (15) Pachanol B R1 = H, R2 = -, R3 = αCH3; △ 11(12), 13 (18) Pachanol C Pachanol D…”
Section: Triterpenes From Mexican Columnar Cactaceaementioning
confidence: 99%
“…Construction of a multitarget parameter should not be based only on the simple average of the in silico or experimental data; for example, highly selective ligands to a single target would appear as multitarget drugs, since the average is a measure sensitive to extreme values. With this in mind, our research group suggested the use of a virtual multitarget parameter, which consisted of a weighted average of the docking scores of potential biopesticides (Loza-Mejía et al, 2018). This analysis proved useful for comparing a ligand's "multitargeticity."…”
Section: Introductionmentioning
confidence: 99%